Family Literacy Program for Improving the Ability to Know Letters in Early Childhood - Mukti Amini (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The ability of children aged 5-6 years old at Mentari Kindergarten, Tangerang, can recognize letters is still not optimal. Parents also do not understand early childhood reading stimulation at home, so it is necessary to carry out a family literacy program. This study aims to improve the ability of children aged 5-6 years to recognize letters through a family literacy program. This type of research is Action Research. Learning activities carried out at Mentari Kindergarten are still carried out online, namely LFH (Learning from Home) with family due to the COVID-19 pandemic. The research subjects were 13 children, consisting of 5 boys and 8 girls. Evaluation of learning activities before and after receiving improvements in the form of checklists and the output of learning outcomes in the form of worksheets and photo evidence of LFH activities. At the end of the study, there was an increase in children's ability to recognize letters well by 80%. These results have exceeded the research success criteria, so it can be concluded that the family literacy program can improve the ability of early childhood to recognize letters.